Rekomendasi Pemanfaatan Marmer Daerah Besole, Kecamatan Besuki, Kabupaten Tulungagung, Provinsi Jawa Timur Berdasarkan Karakteristiknya - Selma Kurniawati; Anastasia Dewi Titisari (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2019)
Besole area, Tulungagung regency, East Java province is an area with measured marble resource potential of 15 million tons. This study aims to determine marble recommendations based on their characteristics. Marble characteristic has brownish white-brown description of megascopis, non-foliated structure, based on fracture density measurement using inventory method, marble has medium density, based on petrographic analysis, marble has crystal size ≤ 0.5 - 2 mm, having texture of metamorphism process resistance ie crystalloblastic and relict, texture of mineral form that is granoblastic, texture of metamorphic rock is decussate and saccharoidal. The composition of marble consists of calcite, dolomite and hematite. Based on analysis of geochemical test using method of ICP-AES (Inductively Coupled Plasma - Atomic Emission Spectroscopy), marble has the main oxide content dominated by CaO 54.6% - 56%, based on the analysis of engineering test yields the average value of compressive strength test of 781,713 kg / cm², wear resistance value 0.0399 mm / min and water absorption value 0.704%. The recommended use of marble based on solid density is utilized as a residential floor with a size of ≤10-40 cm, based on its geochemistry used as paper industry, textile dye, pesticide production, sugar screening and cement production, and based on its technique is used as floor with live load> 250 kg / cm², inner and outer construction stone, and light - medium construction foundation